1992
DOI: 10.1093/geronj/47.4.p266
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Changes in Macrolinguistic and Microlinguistic Aspects of Discourse Production in Normal Aging

Abstract: Middle-aged and elderly healthy subjects were interviewed informally, and their discourse productions were analyzed to test for age-related changes in language-specific, microlinguistic, and in higher order organizational, macrolinguistic abilities. No significant age differences were found on microlinguistic measures, including syntactic complexity and syntactic and lexical production errors, and there were also no age differences in the use of lexical cohesive ties, such as anaphora. Older subjects, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 0 publications
9
143
2
7
Order By: Relevance
“…This dysfunction can appear after damage to left or right prefrontal cortex. Patients with Alzheimer's disease also have narrative deficits (Chapman et al, 2002;Glosser & Deser, 1992). Deficits in narrative production in AD have also been attributed to executive dysfunction, although their episodic memory difficulty makes it difficult to determine the basis for their poor narrative performance.…”
Section: Introductionmentioning
confidence: 99%
“…This dysfunction can appear after damage to left or right prefrontal cortex. Patients with Alzheimer's disease also have narrative deficits (Chapman et al, 2002;Glosser & Deser, 1992). Deficits in narrative production in AD have also been attributed to executive dysfunction, although their episodic memory difficulty makes it difficult to determine the basis for their poor narrative performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, discourse length may be affected by the discourse type: although Juncos-Rabadán et al [34] found that older adults produce longer narrative discourses, Ulatowska et al [35] found that the length of procedural discourses produced by younger and older adults was similar. Glosser and Deser [36] found no difference in lexical production errors between younger and older adults, suggesting that ageing is not associated with more lexical errors. Reduced syntax may occur as a result of healthy ageing.…”
Section: How Language Is Used In Discoursementioning
confidence: 91%
“…Older speakers are likely to produce discourses with less information, or less dense information content, than discourses produced by younger speakers [34,35,43]. Furthermore, when compared to younger speakers, older speakers are likely to produce discourses which are less coherent overall and more likely to contain irrelevant information [34,36,44]. Glosser and Deser [36] measured local coherence, using a method which focuses on how well each utterance relates to the previous utterance, and found that while older adults produced discourse that was less coherent overall, the coherence relationships between neighbouring utterances were the same in younger and older adults.…”
Section: What Information Is Included In Discourse (Coherence)mentioning
confidence: 99%
“…This pattern of reduced grammatical complexity, increased structural complexity, and greater elaboration does not, however, mean that all aspects of discourse become more reader or listener friendly in old age. Decreased cohesiveness and greater likelihood of ambiguous reference have also been reported (e.g., Glosser & Deser, 1992;Kemper, 1990;Kemper et al, 1990;Pratt et al, 1989).…”
Section: Discourse Productionmentioning
confidence: 93%
“…Although older adults do not give off-topic responses with greater frequency than young adults in speech production tasks that do not involve discourse , there have been reports of decreased global coherence associated with less good topical organization (Glosser & Deser, 1992) in older adults. When asked to answer questions about their lives or to narrate personal experiences, older adults do generate longer (more verbose) responses than young adults.…”
Section: Off-target Verbositymentioning
confidence: 97%